A digital agricultural advisory services platform to boost adoption of improved technologies and practices in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets; Spielman, David J.; Abate, Gashaw T. (International Food Policy Research Institute, 2020)
Despite a rapidly growing enthusiasm for the use of information and communications technologies (ICTs) in developing country agriculture, many questions remain on the effectiveness of ICT-based approaches. In the case of Ethiopia, an IFPRI-led and PIM-supported study highlighted the benefits of a large-scale video-mediated approach for agricultural advisory services. The Government of Ethiopia used these results to make a significant investment in digitizing agricultural advisory services.